HOST-GUEST INTERACTIONS IN HUMIC MATERIALS - Smeulders D.E.; Wilson M.A.; Kannangara G.S.K. (My University, 2001)
Dialysis of humic organic matter separates the material into molecular weight fractions or, more correctly, fractions which can pass through specifically sized pores. In the course of investigating the structure of humic organic matter in different industrial processes, we have found some unusual properties of humic fractions from the Bayer process for separating alumina from ferric oxide. The dialysis process appeared not to discriminate against certain small molecules of organic matter produced from a plant operating at 250-255°C. In this paper, we demonstrate that these small molecules appear to be bound to large molecules by physical entrapment and/or noncovalent interactions. Evidence for this supposition is given by proton nuclear magnetic resonance and by derivatisation of polar groups, which then releases the entrapped small molecules that can be detected and identified by gas chromatography/mass spectrometry. A host-guest theory is proposed that may have wide ramifications into the nature of the bonding of other low molecular weight substances to larger humic materials such as those in aqueous solutions in streams, rivers and seas.
Keywords: HUMIC SUBSTANCES; MOLECULAR WEIGHT; BAYER PROCESS; HOST-GUEST THEORY; NUCLEAR MAGNETIC RESONANCE; PYROLYSIS GAS CHROMATOGRAPHY MASS SPECTROMETRY